Socialization and Assistance in the Implementation of Social Assistance for the Dalegan Village Community, Gresik Regency - Kristanto, Titus; Yuniar Rochmah, Wachda; Akhsani Setyo Prayoga, Riza; Mustaqim, Tanzilal; Kamal, Mustafa; Sholik, Mohammad; Rahman, Fandisya; Kusumawati, Aris; Dwi Hariyanto, Muhammad (CV. Pustaka An Nur, 2024)
One of the government's efforts to improve the welfare of the Indonesian people, especially for people living below the poverty line, is the social assistance program. However, some people cannot utilize the social assistance program effectively due to a lack of understanding and access to information about the program. The purpose of community service activities is to increase public awareness and understanding of the various types of social assistance available so that community service activities can help the community in the process of applying for and receiving social assistance. It is expected that the social assistance program will be distributed on target through an approach and assistance involving village officials, community leaders, and direct assistance to village communities. Direct assistance to village communities can also be carried out to ensure that the social assistance distribution information system runs well. The results of community service activities can improve the welfare of village communities, reduce social disparities, increase the transparency of social assistance data, and improve the ability of village officials to manage social assistance. Community service activities can be a model for other villages in managing social assistance.